2016
DOI: 10.4049/jimmunol.1502486
|View full text |Cite
|
Sign up to set email alerts
|

A Histone Methyltransferase ESET Is Critical for T Cell Development

Abstract: ESET/SETDB1, one of the major histone methyltransferases, catalyzes histone 3 lysine 9 (H3K9) trimethylation. ESET is critical for suppressing expression of retroviral elements in embryonic stem cells; however, its role in the immune system is not known. We found that thymocyte-specific deletion of ESET caused impaired T cell development, with CD8 lineage cells being most severely affected. Increased apoptosis of CD8 single-positive cells was observed, and TCR-induced ERK activation was severely inhibited in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 50 publications
0
39
1
Order By: Relevance
“…ATF7ip partners with the histone methyltransferase SETDB1, and the two proteins exert similar effects in HeLa cells with regard to the silencing of zinc finger proteins ( Timms et al, 2016 ). Interestingly, T cell–specific deletion of SETDB1 causes a block in thymic T cell development ( Takikita et al, 2016 ) and augmented Th1 priming ( Adoue et al, 2019 ), while our data show no effect on thymic T cell development or Th1 differentiation. These results imply nonredundant roles for SETDB1 and ATF7ip, and further work will be needed to parse the differential roles of these two epigenetic factors in T cells.…”
Section: Resultscontrasting
confidence: 59%
“…ATF7ip partners with the histone methyltransferase SETDB1, and the two proteins exert similar effects in HeLa cells with regard to the silencing of zinc finger proteins ( Timms et al, 2016 ). Interestingly, T cell–specific deletion of SETDB1 causes a block in thymic T cell development ( Takikita et al, 2016 ) and augmented Th1 priming ( Adoue et al, 2019 ), while our data show no effect on thymic T cell development or Th1 differentiation. These results imply nonredundant roles for SETDB1 and ATF7ip, and further work will be needed to parse the differential roles of these two epigenetic factors in T cells.…”
Section: Resultscontrasting
confidence: 59%
“…Previously researches reported that HOTAIR may indirectly increase the expression of SETDB1 [ 79 ]. As a histone methyltransferaes, SETDB1 is known to repress gene expression in euchromatin through H3K9 trimethylation [ 80 , 81 ], and directly decreased ERK1/2 activity [ 82 ]. In this study, we found that HOTAIR inhibition led to the change of the distribution of MKL1 in HeLa cells, which the expression of nuclear localization of MKL1 was dramatically decreased compared with in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, retroelements repressed by SETDB1 in mESCs, such as IAPs and ETns, are not activated in differentiated cells lacking SETDB1 [48]. However, recent studies of adult Setdb1 KO mice and differentiated cells showed that SETDB1 also represses retroelements in somatic cells: B lymphocytes [49], T lymphocytes [50], brain [51], and iMEFs [52]. Consistent with this, KRAB-ZNF/KAP1, which is a pivotal factor of SETDB1 recruitment to its target regions, also functions in retroelement silencing in adult tissues [53][54][55].…”
Section: Setdb1 Regulates Retroelements Also In Somatic Cellsmentioning
confidence: 99%
“…SETDB1 is also essential for germ cell development [45,56,57], neurogenesis [51], osteoblast differentiation [58], chondrocyte differentiation [59,60], B-cell development [49,61], maintenance of hematopoietic stem and progenitor cells [62], T cell development [50], and restricting the differentiation potential of preadipocytes [38]. Additionally, SETDB1 regulates the expression of tissue-specific genes [38,50,51,62]. Therefore, SETDB1 plays important roles in development, cell differentiation, and other cellular functions by regulating the transcription of both genes and retroelements.…”
Section: In Vivo Function Of Setdb1mentioning
confidence: 99%